Concrete Evidence: Infrastructure Challenges and the COVID-19 Pandemic. (January 2021) - Miller, Robert A.; Klouda, Nolan; Fisk, Jonathan M.
The COVID pandemic has forced governments to reimagine their revenue sources and spending priorities as well as how they balance meeting increasing public health demands with other pressing challenges. As the challenges to local economies have grown, policymakers at all levels of government have debated how best to restore confidence in the economy while mitigating the pandemic's economic fallout. One such example is the Federal Government's CARES legislation, which covers expenses related to COVID mitigation and response for state and local governments. This short commentary examines the experiences of Anchorage, Alaska and Reno, Nevada and offers a 'lessons learned' on how best to stimulate growth while protecting citizens' health.